Pengaruh Indeks Massa Tubuh, Daya Ledak Tungkai dan Motivasi Terhadap Kemampuan Lompat Jauh - Fitra, Muhammad Al; Hudain, Muh. Adnan; Hanafi, Suriah; Adil, Ahmad; Kamaruddin, Ilham (Universitas Hamzanwadi, 2025)
The purpose of this study was to determine whether there is a direct influence of body mass index, leg explosiveness and motivation on long jump ability. This type of research is descriptive research and the method used is survey method with path analysis technique for data analysis. The population in this study were all students of SMP Kartika XX-1 Makassar. The sample was 30 people with the sampling technique, namely probability sampling. The data analysis technique used was descriptive and inferential statistical analysis with SPSS 22. The results of this study indicate that there is a direct effect of body mass index on student motivation 31.3%. There is a direct influence of leg explosive power on student motivation 56.5%. There is a direct effect of body mass index on students' long jump ability 26.2%. There is a direct influence of leg explosive power on students' long jump ability 65.2%. There is a direct effect of motivation on students' long jump ability 32.1%. There is a direct effect of body mass index on students' long jump ability through motivation 10.0%. There is a direct effect of leg explosive power on students' long jump ability through motivation by 18.1%. It is concluded that there is an influence of BMI, leg explosive power, and motivation on long jump ability.